2021
DOI: 10.1123/japa.2020-0078
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an 8-Week Resistance Training Program in Older Adults: A Randomized Controlled Trial

Abstract: Older adults are challenged with aging-related declines in skeletal muscle mass and function. Although exercise interventions of longer duration typically yield larger changes, shorter-term interventions may kick-start positive effects, allowing participants to begin engaging in more activity. This study aimed to determine whether 8 weeks of a resistance training program (Stay Strong, Stay Healthy [SSSH]) improved dynamic muscle strength, balance, flexibility, and sleep. Inactive adults aged ≥60 years were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…Second, many older adults may perceive RT to be difficult and not worth the time. Practitioners need to educate older adults on these data demonstrating acute participation in SSSH can elicit lasting benefits and can kick-start engagement in other forms of exercise ( Baker et al, 2020 ), which may provide additional motivation to improve health. Data from this study support these findings as over half of Repeaters reported engaging in new forms of physical activity and purchased weights for continued at-home resistance training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, many older adults may perceive RT to be difficult and not worth the time. Practitioners need to educate older adults on these data demonstrating acute participation in SSSH can elicit lasting benefits and can kick-start engagement in other forms of exercise ( Baker et al, 2020 ), which may provide additional motivation to improve health. Data from this study support these findings as over half of Repeaters reported engaging in new forms of physical activity and purchased weights for continued at-home resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…SSSH programming has been described elsewhere ( Baker et al, 2020 , 2021 ; Ball et al, 2013 ; Syed-Abdul et al, 2021 ), but in summary the program meets in-person two times per week for 60 minutes, with a warm-up and cool-down. All eight exercises are performed at a 2.4 second tempo and include wide leg squat, leg curl, toe stand, side-leg raise, biceps curl, overhead press, bent-over seated row, and knee extension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants completed pre and post intervention functional assessments that fall into three categories, dynamic postural change, static balance with and without additional challenges, and lower body flexibility. The dynamic postural change tasks included a 30-second sit-to-stand task (30STS) and an 8 foot timed-up-and-go task (TUG) (Baker et al, 2020). The 30STS is reported as the number of full chair stands a participant completes in 30 seconds, is attempted once, and is a test of lower body strength and endurance, dynamic balance, and coordination.…”
Section: Methodsmentioning
confidence: 99%
“…Age-related discrepancies in RT frequency is in-part due to most RT programs being created for and tested on older adults under the age of 70 years (Ball et al, 2013). This discrepancy is significant because deficits in muscle strength, gait, and balance are the most prominent predisposing risk factors for falls and loss of independence and increase in severity as older adults age into their 70's and 80's (Ganz & Latham, 2020) but RT improves these parameters to a greater extent than aerobic training (Baker et al, 2020;Villareal et al, 2017).Most muscle-strengthening and RT programs that are developed specifically for older adults' have been shown to improve muscle capacity and bone integrity (Ball et al…”
mentioning
confidence: 99%